TINJAUAN SARANA DAN PRASARANA JALUR PEDESTRIAN DI KAWASAN PEUNAYONG, BANDA ACEH - Sri Handayani; Mirza Irwansyah; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The pedestrian path is one of the important elements in urban areas. This path is for pedestrian mobility. Accessibility of this path is largely determined by track conditions. This pedestrian path must meet the physical criteria in terms of facilities and infrastructures. The existence of pedestrian path in Peunayong area, which is one of the central business, trade and service center and heritage area, is still not equipped with facilities and infrastructures in accordance with the provisions and requirements of the Ministry of Public Works. In addition, the crowded activities in this region cause the change of pedestrian function into other activities i.e. trading place, parking space. The formulation of the problem in this research is how the condition of pedestrian path facilities and infrastructure in Peunayong area is related to the terms of requirements, standards and accessibility for pedestrians including pedestrians with special needs or pedestrians with physical limitations. The results and discussion of this study are based on the results of observations on the condition of pedestrian path facilities and infrastructure in Peunayong area. A comparison to the standards, rules and literature review is carried out.